Medios de comunicación y propaganda. El caso de Elián González - Labio Bernal, Aurora (Estudios sobre el Mensaje Periodístico, 2003)
At the end of November 1999, eleven people died when a little boat that comes out from Cuba to USA sank near the American coast. It was not the first time that an event likes that happens, although in this case there was a special element for international relationships. One child, Elián González, was the only survivor of the shipwreck and he became in the central point of the old differences between United States and Cuba. This article analyses the treatment of the case in American and Cuban media. The objective is to point out how the information was under propaganda purposes against the real interest of the child.
Keywords: Elián González Information Propaganda United Status Cuba